2015
DOI: 10.12816/0031573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heat Tolerance in Bread Wheat Using Some Agronomic Traits and SRAP Markers = تقييم التحمل للحرارة في قمح الخبز باستخدام بعض الصفات المحصولية و واسمات SRAP

Abstract: Fifty bread wheat lines were evaluated for heat tolerance and compared to some local cultivars under three sowing dates (November 25th, December 15th and January 5th). Four agronomic traits were evaluated, i.e. No. of spikes per plant, grain yield per plant, 100-kernel weight and harvest index under normal and stress conditions. Analysis of variance showed highly significant variations among the tested lines and demonstrating that the main effect of sowing dates was due to the late date. Grain yield per plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…High polymorphic rate and PIC value suggested a high level of heterogeneity among studied barley cultivars. These results agree with those obtained (Said et al, 2015, Mariey et al, 2018, 2021. Since SRAP marker to evaluate the genetic variations among barley and they suggested that SRAP technology is useful for genetic diversity and relationship analyses, marker assisted selection and genetic map construction in barley.…”
Section: Genotypic Diversity Changes Due To Heat Stresssupporting
confidence: 89%
See 2 more Smart Citations
“…High polymorphic rate and PIC value suggested a high level of heterogeneity among studied barley cultivars. These results agree with those obtained (Said et al, 2015, Mariey et al, 2018, 2021. Since SRAP marker to evaluate the genetic variations among barley and they suggested that SRAP technology is useful for genetic diversity and relationship analyses, marker assisted selection and genetic map construction in barley.…”
Section: Genotypic Diversity Changes Due To Heat Stresssupporting
confidence: 89%
“…Accordingly, it is confirmed that the SRAP marker could be efficiently used to assess genetic variation among Egyptian barley and their ability for tolerance to heat stress, which the dendrogram of SRAP markers had clustered all the Egyptian cultivars in to two groups each group include the most closed cultivars together according their response to heat stress. (Said et al, 2015 andAnwer et al, 2021).…”
Section: Genotypic Diversity Changes Due To Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…HT identification is the most basic, critical and difficult part in the HT researches. In some studies, agronomic traits or physiological and biochemical indicators related to HT were used as criteria for HT identification (Said et al, 2015;El-Rawy and Youssef, 2014;Sun et al, 2015a;Jespersen et al, 2018;Priya et al, 2018). In this study, plant appearance (yellow leaves) was taken as the only criterion to evaluate the HT of plants, which could more directly reflect the stress degree of plants and facilitate large-scale identification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in wheat (Triticum aestivum), Moustafa et al (2014) identified SRAP markers linked with six agronomic traits under drought stress. Said et al (2015) detected SRAP markers associated with four agronomic traits related to HT. El-Rawy and Youssef (2014) evaluated the drought and HT in wheat based on seedling traits, and screened the SRAP markers associated with them.…”
Section: Introductionmentioning
confidence: 99%